UPAYA SHADOW TEACHER DALAM MENDUKUNG KEMANDIRIAN BELAJAR DAN PRAKTIK IBADAH SISWA DISABILITAS INTELEKTUAL PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP AL FIRDAUS SUKOHARJO TAHUN AJARAN 2025/2026 - Fitriana Wahyu Wijayanti; Diah Novita Fardani (Jurnal Manajemen Pendidikan, 2026)
This study examines the support efforts of shadow teachers for students with intellectual disabilities within the context of inclusive education. The research focuses on the learning process of Islamic Religious Education and Character Education (PAI-BP). The study was conducted at SMP Al Firdaus Sukoharjo, an institution under the auspices of Al Firdaus World Class Islamic School, which received the Inclusive Education Award from the Ministry of Education. Employing a descriptive qualitative approach, data were collected through observations, semi-structured interviews, and documentation. The findings indicate that shadow teachers strive to adapt the curriculum based on Individualized Education Programs (IEP) by adjusting the complexity of the material and simplifying instructions. Scaffolding efforts are implemented intensively during academic support and the habituation of religious practices, and are subsequently reduced gradually as the students' independence increases. The novelty of this research lies in its analysis of shadow teacher assistance practices through the lens of scaffolding in Islamic Religious Education for students with intellectual disabilities at the inclusive junior high school level.